Minimum recommended micronutrient intake status and associated factors among pastoralist children aged 6–23 months in Aysaita district, Afar Region, Ethiopia, 2024: A community based cross-sectional study - Ali Mohammed Ibrahim; Abdulkerim Hassen Moloro; Dereje Desalegn Boshe; Yeshimebet Ali Dawed (PLoS ONE, 2025)
Background Micronutrient deficiencies are among the most prevalent public health problems in developing countries like Ethiopia. Despite government efforts to address these deficiencies, progress remains slow, leaving many children to endure serious health consequences. There is a scarcity of studies examining the minimum recommended micronutrient intake among children aged 6–23 months in this study area. Objective This study aimed to assess minimum recommended micronutrient intake status and associated factors among pastoralist children aged 6–23 months in Aysaita District, Afar Region, Ethiopia, 2024. Methods A community-based cross-sectional study design was conducted among 614 children aged 6–23 months with mothers from August 1–30/2024. Multi-stage sampling technique was used to select study participants. Data were collected by KoboToolbox using an interview-based structured questionnaire. The collected data were exported to Excel and then into STATA version 17 software packages. Descriptive statistics such as proportion, mean, median, cross-tabulation, and frequencies were calculated and presented in tables. Bivariable and multivariable logistic regression analyses at a 95% confidence interval (CI) and a P-value of less than 0.05 in the multivariable logistic regression were considered significant predictors. Results All study participants were included for data collection by giving a response rate of 100%. In this study, only 35.67% of the children aged 6–23 months had received at least one minimum recommended micronutrient intake status (35.67%; 95% CI: 31.96, 39.54%). Being a male child (AOR = 2.04; 95% CI: 1.42, 2.92), having media exposure (AOR = 2.50; 95% CI: 1.34, 4.64), having exclusive breast feeding (AOR: 5.09, 95% CI: 2.72, 9.52), being in the income category 7.07–35.34 USD (AOR: 2.90, 95% CI: 1.49, 5.65) and spontaneous vaginal delivery (AOR: 2.71, 95% CI: 1.20, 6.10) were factors associated with the minimum recommended micronutrient intake status. Conclusions and recommendations This study revealed low adequate micronutrient intake among children aged 6–23 months, with only slightly over one-third (35.67%) meeting the minimum recommended status. Being a male child, having media exposure, having exclusive breast feeding, being in the income category 7.07–35.34 USD and spontaneous vaginal delivery were factors associated with the minimum recommended micronutrient intake status. To effectively address micronutrient intake, interventions must be more targeted and intensified. This involves strengthening programs that educate mothers on optimal infant and young child feeding, from exclusive breastfeeding to preparing diverse, nutrient-rich foods. Public messaging via community campaigns and media should be expanded to promote affordable, local food options and must explicitly target caregivers of girls to eliminate preferential feeding practices. Finally, to overcome economic barriers, initiatives like women’s economic empowerment, social safety nets, and homestead food production (e.g., kitchen gardens, poultry) should be supported to ensure consistent household access to nutritious food.